2016
DOI: 10.1002/cyto.b.21373
|View full text |Cite
|
Sign up to set email alerts
|

CD19 negative precursor B acute lymphoblastic leukemia (B‐ALL)—Immunophenotypic challenges in diagnosis and monitoring: A study of three cases

Abstract: Background CD19 is a B‐cell specific marker, expressed on all stages of B‐lymphocytes including plasma cells. It is widely used in the flow cytometric immunophenotyping (FCI) of B‐cell and plasma cell malignancies. The analysis approach of FCI for the diagnosis and monitoring of B‐cell acute lymphoblastic leukemia (B‐ALL) is totally based on the CD19‐based primary gating strategy and it would be challenging to study B‐ALL without CD19 expression. Since CD19 negative B‐ALL are extremely rare, we report three ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…CD19de novo B-ALL is very rare but reported. 32,33 A more common scenario is the loss of CD19 because of prior use of CD19-targeted immunotherapy. 11 We found that patients who were previously treated with blinatumomab had a significantly higher rate of failure to achieve MRDremission, and CD19 -MRD/relapse.…”
Section: Discussionmentioning
confidence: 99%
“…CD19de novo B-ALL is very rare but reported. 32,33 A more common scenario is the loss of CD19 because of prior use of CD19-targeted immunotherapy. 11 We found that patients who were previously treated with blinatumomab had a significantly higher rate of failure to achieve MRDremission, and CD19 -MRD/relapse.…”
Section: Discussionmentioning
confidence: 99%
“…At the time that instructions for gating were initially distributed, we did not account for how to analyze dim CD191 cases even though antigen down-regulation has been documented (20)(21)(22). These presented a particular challenge, as this is the primary marker used to identify B-cell populations in the standard COG protocol.…”
Section: Dry Challenge Round 3 (Fig 2c Cases 11-15)mentioning
confidence: 99%
“…In conclusion, we identified CD72 as a novel and robust pan‐acute leukemia TAA, strongly and specifically associated to pediatric BCP‐ALL as well as to half of the AML. Importantly, CD72 expression detected in blasts at diagnosis and at the time of molecular/overt relapse, including those characterized by CD19 loss [24, 25], strongly supports its use for advanced diagnostics. The potential of developing a novel immunotherapy approach with the unique potential of targeting both, acute lymphoid and myeloid leukemias, supports to advance CD72 pre‐clinical testing to provide a specific and selective cellular therapy.…”
Section: Resultsmentioning
confidence: 99%